Nio Modification Using Zr4+ And Ca2+ For Dielectric Improvement - Syedsalim, Sharifah Aishah (2014)
In this research, the effect of Zirconium ions (Zr4+) and Calcium ions (Ca2+) dopant on NiO was investigated. The electroceramic of Ni(l_;c)ZrxO, Ni(l_x)CaxO and Nio.9SZrO.o2CaO.OI was prepared by using solid state reaction method. Three main raw materials ofNiO, Zr02 and CaO were mixed for 24 hours, then were calcined at 1000°C. Ni(l_x)Zr.